A Model On The Role Of Technology In Maritime Security - Ghosh, Sudeeptho (Digital Repository of Theses, 2025)
A wide variety of goods, including raw materials, completed goods, and bulk materials, can be efficiently and affordably transported via maritime routes. In response to the shift in economic power brought about by "Globalisation" and the proliferation of trade-friendly policies, the shipping sector has been providing first-rate services to customers all over the world. The overarching goal of this research is to assess the maritime industry's susceptibility to maritime crimes, including piracy, armed robbery against ships, and maritime terrorism, by reviewing relevant legal instruments and conducting an internal evaluation. The approach applied in this research entails qualitative and quantitative data by interviewing the main maritime stakeholders such as the administrative officers, law enforcement, and the shipping companies, and using surveys and statistical testing. Questionnaires were administered to a diverse sample of maritime stakeholders: foreign navies, coast guards, and shipping companies, so as to achieve a cross-sectional view of the status of maritime security worldwide. According to the findings, all the participants agree that more should be done to improve maritime security and measures, but they are divided regarding International Maritime Organization (IMO) norms and standards. Certain areas face considerable problems in exchanging information, including data about security threats and the results of the analysis, in real-time, which is important for a timely reaction. Furthermore, measures like the “Ship Security Alarm System” (SSAS), “Automatic Identification System” (AIS) and “Vessel Traffic System” (VTS), although useful in effectiveness, are reduced by the differences in the development of facilities and training between regions thus, leading to inconsistency in the measure taken. The study concludes that a contextually adaptive approach to maritime security, one that considers regional capabilities and specific threat levels, is essential for improving global maritime safety. Rather than a one-size-fits-all solution, the research suggests region-specific adaptations to IMO standards and improved coordination between administrative, enforcement, and operational stakeholders. This work is useful for policymakers and maritime agencies trying to improve their security measures and creates a basis for subsequent academic research on regional and technological developments of maritime security.